2021
DOI: 10.1088/1475-7516/2021/09/012
|View full text |Cite
|
Sign up to set email alerts
|

Small field polynomial inflation: reheating, radiative stability and lower bound

Abstract: We revisit the renormalizable polynomial inflection point model of inflation, focusing on the small field scenario which can be treated fully analytically. In particular, the running of the spectral index is predicted to be α = -1.43 × 10-3 +5.56 × 10-5(NCMB-65 ), which might be tested in future. We also analyze reheating through perturbative inflaton decays to either fermionic or bosonic final states via a trilinear coupling. The lower bound on the reheating temperature from successful Big Bang … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…It has been recently shown that such a polynomial inflection-point inflationary scenario fits easily consistent with current CMB observations with rather large parameter space [53]. Additionally, the inflationary predictions can be analyzed analytically even though the model includes several free parameters [53]. A notable prediction is that the running of the spectral index α ∼ O(10 −3 ), making this small field inflationary model testable in the near future [54].…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…It has been recently shown that such a polynomial inflection-point inflationary scenario fits easily consistent with current CMB observations with rather large parameter space [53]. Additionally, the inflationary predictions can be analyzed analytically even though the model includes several free parameters [53]. A notable prediction is that the running of the spectral index α ∼ O(10 −3 ), making this small field inflationary model testable in the near future [54].…”
Section: Introductionmentioning
confidence: 53%
“…The polynomial nature of the inflaton potential is a key difference from the usually considered monomial scenarios, which has been gaining interests since the 1990s [48][49][50][51][52]. In the minimally coupled scenario, the flatness of a polynomial potential of quartic order is guaranteed by the existence of a (near) inflection-point [53]. It has been recently shown that such a polynomial inflection-point inflationary scenario fits easily consistent with current CMB observations with rather large parameter space [53].…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations